2001
DOI: 10.1067/mhn.2001.113663
|View full text |Cite
|
Sign up to set email alerts
|

Posterior petrous face meningiomas

Abstract: Patients with large tumors emanating from the posterior fossa aspect of the temporal bone should be evaluated on the basis of their site of origin. Patients with tumors emanating from the anterior or ventral portion of the temporal bone have greater symptoms and greater operative complications than those emanating from the posterior petrous face, between the porus acousticus and sigmoid sinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The largest tumor diameter on CT scans and/or MR images defined the tumor size, which was categorized as small (Ͻ 3 cm, 13 [16%] of 82 lesions), medium (3-4 cm, 14 [17%] of 82 lesions), and large (Ͼ 4 cm, 55 [67%] of 82 lesions). All patients had undergone CT scanning and/or MR imaging studies, and a comparison of tumor size based on imaging results is featured in Table 2.…”
Section: Neuroradiological Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest tumor diameter on CT scans and/or MR images defined the tumor size, which was categorized as small (Ͻ 3 cm, 13 [16%] of 82 lesions), medium (3-4 cm, 14 [17%] of 82 lesions), and large (Ͼ 4 cm, 55 [67%] of 82 lesions). All patients had undergone CT scanning and/or MR imaging studies, and a comparison of tumor size based on imaging results is featured in Table 2.…”
Section: Neuroradiological Evaluationmentioning
confidence: 99%
“…Most investigators hold the same view. 2,[11][12][13] Yasargil, et al, 16 asserted that meningiomas in this region should be classified into anterior petroclival meningiomas and posterior CPA meningiomas. Schaller, et al, 12 reported on 31 CPA meningiomas and divided them into premeatal and retromeatal meningiomas.…”
Section: Definition and Classification Of Posterior Petrous Meningiomasmentioning
confidence: 99%
“…However, when located adjacent to eloquent brain or cranial nerves, or when they grow large enough, they can produce local mass effect and become symptomatic. 2 The primary treatment is surgical resection or radiotherapy with excellent outcomes. 3 Tumors in challenging locations, such as deep along the skull base and around the cranial nerves, have higher rates of subtotal resection and complications.…”
Section: Introductionmentioning
confidence: 99%
“…3 Tumors in challenging locations, such as deep along the skull base and around the cranial nerves, have higher rates of subtotal resection and complications. 2,46 Meningiomas in the cerebellopontine angle grow from the petrous face and are surgically challenging due to their proximity to the brainstem, posterior fossa vasculature and cranial nerves (CN). 2,5,7 The primary approaches for surgical resection of petrous face tumors are the retrosigmoid, far-lateral and transpetrosal approaches, which are selected based on tumor location along the petrous face.…”
Section: Introductionmentioning
confidence: 99%
“…Microsurgery is considered to be the gold standard in treating intracranial meningiomas (1,5,6,12). Meanwhile, even if those benign tumors are slightly radiosensitive (2), the place of radiation therapy in treatment algorithm has recently evolved, with the dramatic development of 3-D conformal dosimetry, such as fractionated radiation therapy, LINAC radiosurgery, or gamma knife radiosurgery (13Y16).…”
Section: Discussionmentioning
confidence: 99%